Determination of Cefalexin by Direct (UV- Vis) Spectrophotometer and Indirect(Flame Atomic Absorption) Technique - Amera A. Mohammad (College of Pharmacy University of Baghdad, 2017)
A new method for the determination of the drug cefalexin in some Pharmaceuticals using (UV-Vis) and  indirect Flame Atomic Absorption Spectrophotometer (FAAS) , Fe III should forms a chelating complex with cefalexin (CEX â€"Fe III) at pH (1-8) and the best pH for the formation of (CEX â€"Fe III) chelating complex was (2) .The complex extracted with Methanol  and  Dimethy-Sulphoxide .The mole-ratio method has been used to determine the structure of chelate (CEX - Fe III) and found to be 2:1 LM ( Ligand : Metal.) . Keywords : Cefalexin , chelating complex.